The Impact of it Strategic Planning on Human Resource Management Information System - Hakimeh Shahriyari (Journal of Global Pharma Technology, 2017)
The objective of this study is to investigate the impact of IT strategic planning on Human Resource Management Information System. This is a descriptive-analytical research and in terms of objective, this is an applied study. The statistical population of this study consists of all managers, supervisors and experts in Zabol University of Medical Sciences. Data collection tool is questionnaire with content validity and the overall reliability of 0.81 that is calculated using Cronbach’s alpha. The results of this study showed that there is a positive and significant relationship between IT strategy and factors of “coordination of tasks in the Human Resource Information System”, “Interaction between beneficiaries of information”, “Maturity of information systems” and “Focus on organizational structure” with respectively Pearson’s correlation coefficients of 0.43, 0.45, 0.33, and 0.45.